Exploring Voice Barriers And Subsequent Practices Among Frontline Healthcare Workers In Pakistan: A Comprehensive Mixed-methods Analysis - Noreen Kanwal; Ahmad Shahrul Nizam Isha; Al-baraa Abdulrahman Al-Mekhlaf; Rao Irfan Ali Haider (Springer Nature, 2025)
Indexed Publication (Tier 2)